The Relevance of Lev Vygotsky's Constructivist Theory to the Islamic Religious Education Learning System in Indonesia - Ariansyah, DD Alija (Mudir : Jurnal Manajemen Pendidikan, 2023)
This research discusses the relationship of Lev Vygotsky's constructivist theory to Islamic Religious Education (PAI) learning in Indonesia. In some cases, it is still found that the implementation of PAI learning is carried out through the indoctrination method. Students are given a